(3GdJPcQI aj CMcGe GdLhGgQ hGdCYQGVs - (3Ydj Hf CMeO Hf eMeO Hf Ydj Hf neoqJhjI, CHh GdMSf GdhGMOj,J (B468 (3g` s ((3eOQSI XaGQ GdeMQS s)
(3ChdgG (B:s
(3Gddge EfG fSJgO Hc WQjb GdMb hfSdc GdJhajb ddUOb gPg JPcQI JTJed Ydi HjGf CMcGe GdeYdheGJ hChUGagG hJLeY Edi GdEjLGR ai Gdbhd GSJbUGA ai GdCOdI s
(3BNQgG (B:s
(3hgPG BNQ GdcdGe GdCYQGV GdeNJUg HGdeMGd hGdMeO ddg Je GdLRA GdChd ef cJGH GdJPcQg ai CMcGe GdLhGgQ hGdCYQGV s
(3GdfSNI HgG MhGTs
(3fSNI Chdis
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B255 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B26 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B692s
Keywords: (3GdcjejGA h GdWHjYjGJs